2017
DOI: 10.1038/s41598-017-13887-y
|View full text |Cite
|
Sign up to set email alerts
|

The histone variant H3.3 G34W substitution in giant cell tumor of the bone link chromatin and RNA processing

Abstract: While transcription as regulated by histones and their post-translational modifications has been well described, the function of histone variants in this process remains poorly characterized. Potentially important insight into this process pertain to the frequently occurring mutations of H3.3, leading to G34 substitutions in childhood glioblastoma and giant cell tumor of the bone (GCTB). In this study, we have established primary cell lines from GCTB patients and used them to uncover the influence of H3.3 G34W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 53 publications
10
41
0
Order By: Relevance
“…We also reported that Rpp29 depletion increases H3.3 chromatin deposition and sense (S) and AS RNA levels, which suggests that an RNase P variant represses H3.3 chromatin assembly and transcription. Consistent with our results, a recent study identified RNA proteins, including RPLs and splicing factors, as H3.3-interacting factors (40). This study also showed that H3.3(G34W) increases chromatin compaction and causes aberrant RNA processing.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…We also reported that Rpp29 depletion increases H3.3 chromatin deposition and sense (S) and AS RNA levels, which suggests that an RNase P variant represses H3.3 chromatin assembly and transcription. Consistent with our results, a recent study identified RNA proteins, including RPLs and splicing factors, as H3.3-interacting factors (40). This study also showed that H3.3(G34W) increases chromatin compaction and causes aberrant RNA processing.…”
supporting
confidence: 92%
“…Several, including the GCTB mutation, G34W, increase the affinity for Rpp29. Of interest, H3.3(G34W) has been reported to down-regulate transcription and increase chromatin compaction (40). Because we show that Rpp29 promotes heterochromatic PTM deposition, it is possible that H3.3(G34W) promotes tumorigenesis by enhancing the gene-silencing function of Rpp29.…”
Section: Rpp29 Regulates H33 Through Transcriptional Mechanismsmentioning
confidence: 68%
“…For GCTB, the genes undergoing a change upon redistribution of the H3K36me3 marks as a result of the H3F3A G34W/L mutations remain to be identified. Changes that are observed in primary GCTB cells harbouring a G34W mutation are increased proliferation, migration and colony formation capacity as compared to wild-type counterparts [55,56]. Furthermore, splicing aberrations and alternative transcription start sites are frequently observed in H3F3A G34W-mutated cells, suggesting an alteration in the RNA processing pathway [55].…”
Section: Idh1 R132hmentioning
confidence: 99%
“…Changes that are observed in primary GCTB cells harbouring a G34W mutation are increased proliferation, migration and colony formation capacity as compared to wild-type counterparts [55,56]. Furthermore, splicing aberrations and alternative transcription start sites are frequently observed in H3F3A G34W-mutated cells, suggesting an alteration in the RNA processing pathway [55]. Future studies are needed to elucidate which genes and signalling pathways are affected by the H3F3A G34 mutationdriven epigenetic alterations.…”
Section: Idh1 R132hmentioning
confidence: 99%
“…Together we collected data from analysis platforms with the ambition to understand the function of H3.3 in cancer ( Fig. 1c ), which in part has been described in a previous publication 7 .…”
Section: Background and Summarymentioning
confidence: 99%